Identification of the learning characteristics of the Primary Education students with the CEAPS questionnaire - Maquilón Sánchez, Javier J.; Hernández Pina, Fuensanta (Anales de Psicología / Annals of Psychology, 2010)
The analysis of the relation between motivation and learning strategies used by students has been undertaken in various different contexts following the SAL model (Student Approaches to Learning). Researchers like Biggs, Watkins, Kember, and Hernández Pina, in the Spanish context, among others, have established the empirically above-mentioned relation. The age of the students is a determinant factor at the moment of analyzing the approaches of learning. The originality of this research is that has been realized by students of Primary Education using a new questionnaire of approaches to learning designed and validated specifically for this study, we refer to the CEAPS.